Phenomenology Study: Community Perception Of Lush Disease In The Working Area Of Puskesmas Talango, 2020 - Mukhlish Hidayat; Diana Irawati; Agung Waluyo (Universitas STRADA Indonesia, 2020)
Leprosy (Morbus Hansen) is a chronic infectious disease of the skin caused by Mycobacterium leprae, leprosy is also known as